Bevacizumab as an Adjunct to Trabeculectomy in Primary Open-Angle Glaucoma: A Randomized Trial - Alper Bilgic; Aditya Sudhalkar; Anand Sudhalkar; Megha Trivedi; Viraj Vasavada; Shail Vasavada; Vaishali Vasavada; Samaresh Srivastava (Journal of Ophthalmology)
Purpose. To compare the outcomes of trabeculectomy using two different routes of bevacizumab administration as an adjunct in patients with primary open angle glaucoma. Methods. Prospective, randomized, masked trial that included 180 eyes of 180 patients of documented primary open angle glaucoma were eligible for surgery. Patients were randomized to receive either a single intraoperative dose of subconjunctival bevacizumab (1.25 mg, Group I) or topical bevacizumab (5 mg/ml) for 30 days (Group II). One eye was randomly selected, if both were eligible for surgery. All patients underwent a complete ocular and systemic examination. Bleb morphology was examined and scored as per Moorfields system (MBGS) at 1, 3, 6, 12, 18, and 24 months postoperatively. Visual field, fundus photography, and disc analysis were performed. Outcome measures (at one year) included (1) comparison of bleb morphology in both groups, (2) proportion of patients achieving surgical success, and (3) side effects of treatment. Results. The groups did not differ with respect to age, sex, and crystalline lens status. Group II patients had significantly lower vascularity scores for central (P=0.042) and peripheral bleb areas (P=0.023) and peripheral nonbleb area (P=0.03). A significantly larger proportion of Group II (n = 88) patients achieved average vascular scores of less than 2.5 (P=0.0056, Fisher’s test) than Group I (n = 85). The groups did not differ in terms of surgical success (96% vs. 94%; P=0.54). No major complications were noted in either group. Conclusion. Topical bevacizumab gives a better vascularity profile at one year, but the studied routes appear equally safe and do not seem to affect the outcome in any other way.